2021
DOI: 10.3390/jcdd8120167
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Registry Analysis on Hospitalized COVID-19 Patients with Previous Cardiovascular Disease: Clinical Profile, Treatment, and Predictors of Death

Abstract: A high percentage of patients with COVID-19 (coronavirus disease 2019) have previous cardiovascular disease (CVD). The findings presented here came from an epidemiological population-based registry study (real-world data) that enrolled all in-hospital COVID-19 patients with previous CVD from 1 March to 31 May 2020. Death, other comorbidities, hospital stay variables, ventilation type, and main clinical outcomes were evaluated. In Castile and Leon, 35.83% of the 7307 in-hospital COVID-19 patients who participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Furthermore, tocilizumab and steroids were associated with a low rate of hospital death, which confirm them today the main treatment for SARS in patients hospitalized for COVID-19. Finally, the findings of this study, combined with those previously reported for other clinical conditions with bad prognosis in hospitalized COVID-19 patients (AKI [13] and previous CVD [14]), are decisive for the early detection of patients at risk, to determine the main predictors of mortality and to establish a protocol for clinical and pharmacological management based on previous experience.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Furthermore, tocilizumab and steroids were associated with a low rate of hospital death, which confirm them today the main treatment for SARS in patients hospitalized for COVID-19. Finally, the findings of this study, combined with those previously reported for other clinical conditions with bad prognosis in hospitalized COVID-19 patients (AKI [13] and previous CVD [14]), are decisive for the early detection of patients at risk, to determine the main predictors of mortality and to establish a protocol for clinical and pharmacological management based on previous experience.…”
Section: Discussionmentioning
confidence: 52%
“…In this regard, the main aim of this study is to provide realworld data about in-hospital COVID-19 patients affected by SARS in our region, the largest of Spain, with 2,323,770 inhabitants and a network hospital capacity of 7141 beds spread over 14 hospitals (three regional hospitals, six general hospitals and five first-level referral hospitals). As a continuation of previously conducted research [3,13,14], this manuscript presents an analysis of patterns of drug use, survival, mortality rate and main predictors of mortality among the patients described above. These results complete the in-depth analysis of clinical conditions with worse prognosis for hospitalized COVID-19 patients, such as SARS, acute kidney injury (AKI) [13] and previous cardiovascular disease (CVD) [14].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Since the outbreak of the global COVID-19 pandemic, numerous risk factors of SARS-CoV-2 infection severity have been described [ 1 , 2 ]. Even though several scoring systems [ 3 ] have been proposed, the clinical course among individuals with COVID-19 is still unpredictable.…”
Section: Introductionmentioning
confidence: 99%